Evaluation of the Emergency Remote Learning of Veterinary Anatomy During the COVID‐19 Pandemic: Global Students’ Perspectives - Mahdy, Mohamed A. A.; Ewaida, Zamzam M. (Frontiers in Education, 2022)
Purpose: The present study assessed the shift to remote teaching of veterinary anatomy during COVID‐19 pandemic based on students’ perspectives. Methods: Participants were invited to answer an anonymous online Google Form questionnaire using the snowball sampling method. Only students who studied anatomy online during COVID-19 lockdown period were eligible to answer the questionnaire. Results: A total of 961 participants were enrolled in this study from 87 countries and 6 continents. Data showed that the majority of students (81.6%) were interested in studying anatomy online during COVID-19 lockdown. Moreover, approximately 82% of students were comfortable with the technological skills and approximately 61% of students can understand online anatomy well during lockdown. Furthermore, approximately 52.76% of students believed that online learning of anatomy suited for theoretical, 8.74% believed that it suited for practical parts, and 30.28% believed that it suited for both theoretical and practical parts. On the contrary, about 36.63% of students thought that online learning of anatomy could replace face-to-face teaching. In conclusion, shifting to remote teaching appears to be a good and convenient approach during lockdown period as shown by student interest to study anatomy online during COVID-19 lockdown, their comfortability with the technological skills, and their level of understanding. However, practical classes with cadaver dissection and dealing with different anatomical specimens is essential for veterinary students, therefore, blended learning is recommended. Conclusion: the study highlighted several challenges associated with studying anatomy online during lockdown period and recommendation to overcome these challenges.